Tantangan Pembelajaran Virtual Di Tengah Pandemi Covid-19 Bagi Siswa Sekolah Dasar - Winda Yana; Prima Ayu Rizqi Maharani (Universitas Merdeka Madiun, 2020)
Abstract— Covid-19 is a virus that has been struck all of countries in this world, including Indonesia. The pandemic of Covid-19 virus has changed various aspect of human life, especially in education. In this situation, all elements must be able to adopt and continue learning activities. The purpose of this article is to provide an overview of the various challenges of learning activities during the Covid-19 pandemic. Virtual learning is the most appropriate one to continue teaching learning process even without meeting directly. However, virtual learning model still needs evaluation because not all parents are able to provide facilities which are needed by the students. Therefore, learning techniques that is used must be adjusted with the students’ ability so that teaching and learning activities can run effectively. Keywords—: Covid-19; Pandemic; Virtual Learning.